QUICK SAYS AND TOTEMISTIC ELEMENTS IN THE ORAL CREATION OF TURKISH PEOPLES (Universal International Scientific Journal, 2026)
This article analyzes the role of tongue-twisters in the oral folklore of Turkic peoples,focusing on speech development, pronunciation exercises, and cultural-symbolic content. Itdemonstrates that tongue-twisters are significant not only as phonetic exercises but also as artistic andaesthetic tools
Keywords: Quick sayings; oral creativity; Turkic peoples